ĐÁNH GIÁ HIỆU QUẢ CỦA VIỆC SỬ DỤNG N-ACETYLCYSTEINE TRONG ĐIỀU TRỊ BỆNH NHÂN SUY GAN CẤP DO NGỘ ĐỘC : EVALUATION OF THE EFFICACY OF N-ACETYLCYSTEINE IN THE TREATMENT OF PATIENTS WITH ACUTE LIVER FAILURE DUE TO POISONING (Vietnam Journal of Community Medicine, 2026)
Background: Acute liver failure (ALF) is a dangerous clinical syndrome associated with high mortality rates, most commonly resulting from acetaminophen poisoning. N-acetylcysteine (NAC) has been proven effective in the treatment of acetaminophen-induced ALF, and recent studies have also demonstrated that NAC improves survival without the need for liver transplantation in patients with non-acetaminophen-induced ALF.Objective: To evaluate the therapeutic efficacy of N-acetylcysteine in patients with poisoning-induced acute liver failure.Subjects and Methods: A descriptive, longitudinal follow-up study without a control group was conducted on 41 patients with poisoning-induced ALF at the Poison Control Center, Nghe An General Friendship Hospital, from September 2024 to July 2025. All patients received intravenous N-acetylcysteine according to the established protocol. Treatment efficacy was assessed using SOFA and MELD scores, grade of hepatic encephalopathy, as well as biochemical and coagulation parameters before and after NAC administration.Results: The primary causes of poisoning-induced ALF were attributed to two main agents: paracetamol poisoning accounted for 39.1% of cases, while traditional herbal medicine poisoning accounted for 51.2%. Following NAC treatment, the grade of hepatic encephalopathy decreased from 1.73 ± 0.74 to 1.46 ± 0.51 (p
Keywords: Poisoning-induced acute liver failure, N-acetylcysteine.